2007
DOI: 10.1080/00016480600606665
|View full text |Cite
|
Sign up to set email alerts
|

An effective management regimen for laryngeal granuloma caused by gastro-esophageal reflux: combination therapy with suggestions for lifestyle modifications

Abstract: According to our previous study, lifestyle modification in combination with drug therapy is much more effective than drug therapy alone in cases of laryngopharyngeal reflux (LPR). Most patients with LPR will have chronic gastro-esophageal reflux diseases (GERD) and require long-term medical therapy for control, resulting in high total expenditure on pharmacologic agents. We combined pharmacologic management with lifestyle modifications for the management of GERD with successful outcomes in patients with GERD-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 16 publications
0
27
0
1
Order By: Relevance
“…A single daily dose of PPI together with lifestyle modifications for 8 weeks has been recommended for the majority of patients with LPR symptoms [49]. The PPI dose might be reduced after 8 weeks while maintaining lifestyle modifications [47 ]. Reichel et al [51 ] reported adequate control of LPR symptoms after once-daily PPI for 13-54 days (mean, 28 days) with lifestyle modifications.…”
Section: Treatment Of Laryngopharyngeal Refluxmentioning
confidence: 98%
See 1 more Smart Citation
“…A single daily dose of PPI together with lifestyle modifications for 8 weeks has been recommended for the majority of patients with LPR symptoms [49]. The PPI dose might be reduced after 8 weeks while maintaining lifestyle modifications [47 ]. Reichel et al [51 ] reported adequate control of LPR symptoms after once-daily PPI for 13-54 days (mean, 28 days) with lifestyle modifications.…”
Section: Treatment Of Laryngopharyngeal Refluxmentioning
confidence: 98%
“…Lifestyle modifications include avoidance of heavy meals, smoking, excessive alcohol and meals at night time. Other measures include reducing body weight, avoiding tight clothes and adopting a higher head position in bed [46,47 ]. Anti-acid medications include histamine H 2 receptor antagonists and PPIs, which are superior to other anti-acids in achieving gastric acid suppression [2].…”
Section: Treatment Of Laryngopharyngeal Refluxmentioning
confidence: 99%
“…If medical treatment fails, laparoscopic fundoplication is an alternative. [8] Our patient was inadvertently given double PPI treatment at high dose and the LG resolved quickly without voice therapy. [8] During the treatment period, he obeyed the rules of vocal hygiene and was at complete vocal rest.…”
Section: Discussionmentioning
confidence: 96%
“…[4] The current literature shows that with these treatment modalities, patients usually recover in 2-20 months. [4,8] For follow-up, patients should undergo a monthly laryngological examination. In patients in whom conservative treatment fails, there is airway obstruction, or the diagnosis is unclear, a biopsy by direct laryngoscopy is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation